Development of soft skills and quality of life analysis for the Association of Grassroots Recyclers (ASORELI) in the city of Liberia, Guanacaste - Mora Mora, Paula (2026)
This work evaluates the quality of life of grassroots recyclers in Liberia and develops a soft skills training plan to promote their inclusion in the formal economic system. It applies a qualitative action research approach with ASORELI’s associates, using open interviews, a focus group, a quality of life questionnaire (Q-LES-Q-18) for five of its members, and a review of regulatory frameworks from the Municipality of Liberia, the Institute of Rural Development (INDER), IMAS (Mixed Institute of Social Aid), INVU (National Institute of Housing and Urbanism), the University of Costa Rica (UCR), Manos Solidarias, and Pasión Por la Vida. The results indicate that despite a positive personal assessment of their quality of life, the recyclers face serious physiological, safety, and social limitations, such as the lack of adequate infrastructure and the formality required by the institutions that should provide support. It is concluded that it is essential to meet basic physiological needs before proceeding with soft skills training. Additionally, it is recommended that institutions relax their requirements for informal groups to improve their future opportunities.